Masha Gessen, Where the Jews Aren’t. The Sad and Absurd Story of Birobidzhan, Russia’s Jewish Autonomous Region (New York: Nextbook; Schocken, 2016), 170 str. (Časopis za suvremenu povijest, 2017)
Prikaz knjige